Colon Mucosa Exhibits Loss of Ectopic MUC5AC Expression in Patients with Ulcerative Colitis Treated with Oral Tacrolimus. (9th April 2013) - Mizoshita, Tsutomu; Tanida, Satoshi; Tsukamoto, Hironobu; Ozeki, Keiji; Katano, Takahito; Ebi, Masahide; Mori, Yoshinori; Kataoka, Hiromi; Kamiya, Takeshi; Joh, Takashi
Abstract : Background . Tacrolimus (FK506) is effective for patients with ulcerative colitis (UC). However, there are few reports on tacrolimus therapy (TT) with respect to the relationship with endoscopic and clinicopathologic findings. Methods . Thirty patients with moderate/severe active UC refractory to or dependent on corticosteroid were treated with oral tacrolimus. The expression of ectopic MUC5AC in the colon was pathologically analyzed before and at 12 weeks after TT, evaluating the Mayo score and steroid-sparing effects. Results . Both mean disease and endoscopic activity index scores were reduced at levels of statistical significance in 26 UC patients receiving more than one month of TT (P < 0.0001 ). The dose of prednisolone was reduced by a statistically significant amount (P = 0.00022 ), and 14 of the 26 patients (53.8%) had steroid-free status 12 weeks after TT. The decrease in ectopic MUC5AC expression in the mucous cells of the colon was significantly associated with endoscopic improvement of inflammation in the UC patients with TT (P = 0.043 ). Loss of ectopic MUC5AC expression was detected in all patients who had complete response. Conclusions . Tacrolimus appears to be effective for the treatment of moderate/severe UC patients. Loss of ectopic MUC5AC expression may be important for pathologic remission in the colon of UC patients.